(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2016)
Today, intercultural education is an integral part of foreign language teaching, but there is still controversy about the appropriateness and possibility of implementing this aspect in the process of learning foreign languages ​​in preschool age. Observation of foreign language classes in several preschool institutions in Belgrade, it was found that children at that age may have prejudices and negative attitudes towards other cultures, as well as that teachers are often unaware of the importance of developing intercultural competence in students and miss opportunities. for work in that field, which is primarily a consequence of their inadequate training.